2019
DOI: 10.21037/atm.2019.07.94
|View full text |Cite
|
Sign up to set email alerts
|

Approach to Cushing’s syndrome in pregnancy: two cases of Cushing’s syndrome in pregnancy and a review of the literature

Abstract: Cushing's syndrome (CS) rarely occurs during pregnancy. The primary aim of this article is to propose a therapeutic approach to CS in pregnancy. Here, we present two cases of CS in pregnancy and a literature review. This article proposes the early diagnostic points, especially the clinical approach to this medical condition, mainly for pregnant women without a previous diagnosis of CS. More importantly, we present therapeutic strategies for CS during pregnancy, especially glucocorticoid replacement for periope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Earlier studies have shown a female dominance in patients with CS, Cushing's disease, and unilateral adrenal adenomas, but a balanced sex ratio in PBMAH patients (2,10,11). PBMAH patients usually present at their 50 to 60 years, often older than those with PPNAD, Cushing's disease, and UAA (1,2,12,13). The time from the first symptoms of PBMAH to the diagnosis can be about 7.8 years (13).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Earlier studies have shown a female dominance in patients with CS, Cushing's disease, and unilateral adrenal adenomas, but a balanced sex ratio in PBMAH patients (2,10,11). PBMAH patients usually present at their 50 to 60 years, often older than those with PPNAD, Cushing's disease, and UAA (1,2,12,13). The time from the first symptoms of PBMAH to the diagnosis can be about 7.8 years (13).…”
Section: Discussionmentioning
confidence: 96%
“…In Cushing's disease, the bilateral adrenal hyperplasia is ACTH-dependent, and the plasma ACTH levels are elevated. DST is useful in differentiating Cushing's disease and PBMAH (1). Primary aldosteronism and pheochromocytoma can also cause bilateral adrenal hyperplasia but lack the excessive cortisol production, which is distinct from PBMAH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, physicians face a clinical overlap, in which many features of CS (weight gain, fatigue, edema, hypertension, hyperglycemia, stretch marks, mood changes etc.) can also be attributed to pregnancy (2,3,4). Thus, their coexistence represents a diagnostic challenge.…”
Section: Introductionmentioning
confidence: 99%